Performance of High Strength Concrete Containing Fine Metakaolin, Palm Oil Fuel Ash and Coal Bottom Ash as Substitute Material Towards Mechanical Properties - Che Rahim, Nur Anis Natasha; Ismail, Mohd Hanif; Abu Bakar, Muhammad Nur Rasyid; A. Majid, Masni; Md Noor, Nurazuwa; George, Ambros Francis (International Journal of Integrated Engineering, 2024)
The increased use of high-strength concrete in the construction industry causes a significant amount of cement production that contributes to major carbon dioxide (CO2) emissions. However, various additives such as fine metakaolin (FMK), palm oil fuel ash (POFA), and coal bottom ash (CBA) can be used to improve concrete performance and reduce carbon footprint. A portion of cement in the concrete was replaced with 20% of FMK and various percentages of POFA (5%, 10%, 15%, and 20%) by weight. While sand was replaced with 10% of CBA. Slump test, water absorption test, compressive strength test, flexural strength test, and split tensile strength tests were performed on concrete samples comprising FMK and POFA as cement replacements and CBA as sand replacements in this research. The partial replacement of FMK and POFA for cement and sand for CBA decreased the workability of the concrete. The small particle size of FMK and POFA serve as fillers, reducing concrete’s water absorption. The replacement of POFA by 10% shows the highest compressive strength compared to the control sample. However, water absorption, flexural strength, and split tensile strength improved with the addition of up to 20% POFA. This proves that the incorporation of FMK, POFA, and CBA causes the reaction of alumina oxide, silica oxide, and calcium oxide with calcium hydroxide (C-H) from cement with water during the hydration process of the concrete.